A framework for semantic knowledge representation of Al-Quran based on word dependencies - Mohamad Khazani, Muhammad Muhtadi; Mohamed, Hassan; Mohd Yusop, Nurhafizah Moziyana; Tengku Sembok, Tengku Mohd; Wani, Sharyar; Mohamed Halip, Mohd Hazali; Marzukhi, Syahaneim; Yunos, Zahri (IEEE, 2021)
A variety of applications have been built in recent years with the aim to extract knowledge from Al-Quran. Current knowledge representations of Al-Quran give attention primarily on conceptual ontology models that describe the semantic relations between the Quranic concepts or entities. There seems to be minimal effort towards recognizing the semantic relations between words in Quranic text, which is relatively more complex. This paper aims to present a framework for semantic knowledge representation of AlQuran using dependency relations between words, in an attempt to boost the retrieval accuracy for Al-Quran. The semantic analysis is performed on Quranic verses according to word dependency relations using dependency parsing. Based on parsed dependencies, a set of rules are formulated to build a semantic graph of Surah Ali Imran of Al-Quran. The efficiency of the semantic representation was tested by developing a prototype question answering system. The framework was evaluated using precision and recall, First Hit Success, First Answer Reciprocal Rank and Total Reciprocal Rank by comparing the retrieved and actual answers. The results indicate that the performance of the proposed framework using word dependencies improves the semantic representation of knowledge.